PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) OLEH DINAS SOSIAL KOTA PEKANBARU TAHUN 2020-2022 - Mahdalena, Desi; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Poverty remains one of the major social issues in Pekanbaru City. As an effort to address this problem, the government implements the Family Hope Program (Program Keluarga Harapan/PKH), which is expected to improve the welfare of poor families through support in education, health, and social sectors. This study aims to examine and analyze the implementation of PKH by the Pekanbaru City Social Service during the period 2020–2022. This research employed a qualitative method with data collected through interviews, observation, and documentation. The data were analyzed using William N. Dunn’s policy evaluation theory, which includes effectiveness, efficiency, adequacy, responsiveness, and accuracy, in order to provide a comprehensive picture of the program’s implementation. The results show that PKH in Pekanbaru City has been carried out in accordance with general guidelines and has provided tangible benefits for beneficiary families, particularly in supporting children’s education and maternal and child health. However, the number of poor people increased from 30.40 thousand in 2020 to 35.96 thousand in 2022. This indicates that PKH functions more as a social safety net than as a primary instrument for poverty reduction. Overall, the program can be considered effective and efficient, although it still faces challenges related to data accuracy, limited facilitators, and delays in disbursement. Keywords: Effectiveness, Family Hope Program, Policy Evaluation